Implikasi Hermeneutika dalam Reinterpretasi Teks-teks Hukum Islam - Ridwan, Ahmad Hasan (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract: The Contribution of Hermeneutics in re-Interpreting Islamic Legal Texts. This article examines the contribution of Hermeneutics in reinterpreting the Islamic legal texts. Hermeunetcs enters the treasures of Islamic law through active dialogs between Muslim and Western scholars, and later It becomes an integral part of the of religious discourse in understanding religious texts critically. Among a number of Muslim exponents actively offering new models of interpretation are Sayhrur and Abu Zaid. Shahrur, with the his boundary limit theory, and Abu Zaid, with his significance of intelectual meaning theory, have inspired Muslims to initiate the reform movement of thought as a critical response to the discourse of Islamic law. In the model of this new legal interpretation, hermeneutics becomes an alternative method when the traditional interpretation of Islamic legal thought fails to understand contemporary reality through the interpretation of legal texts. Abstrak: Implikasi Hermeneutika dalam Reinterpretasi Teks-teks Hukum Islam. Artikel ini menelaah tentang kontribusi Hermeneutics dalam telaah ulang terhadap teks-teks hukum Islam. Hermenetika masuk dalam khazanah hukum Islam melalui dialog sarjana Muslim dan sarjana Barat dan kemudian menjadi bagian integral dari wacana pemikiran keagamaan untuk memahami teks-teks keagamaan secara kritis. Di antara sejumlah eksponen Muslim yang aktif menawarkan model interpretasi yang baru ini adalah Sayhrûr dan Abû Zaid. Syahrûr dengan teori batas dan Abû Zaid dengan teori signifikansi makna telah menginspirasi kaum intelektual Muslim untuk memulai gerakan pembaruan pemikiran sebagai respons kritis terhadap wacana hukum Islam. Di dalam model penafsiran hukum yang baru ini, hermeneutika menjadi suatu metode alternatif ketika sistem penafsiran Hukum Islam tradisional tidak mampu untuk memahami realitas kontemporer melalui penafsiran terhadap teks-teks hukum Islam .